FAKTOR PENENTU KEPUTUSAN KONSUMEN DALAM MEMILIH LAYANAN TRANSPORTASI ONLINE DI KOTA MATARAM - I Putu Agus Agus Wiradana; Ni Nyoman Satya Widari; Ni Nyoman Suli Asmara Yanti (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
Traffic on the Internet. This suggests the presence of community or drivers ofconsumer choice for online products. This way we can get interesting researchon price, service quality, corporate image and word of mouth. This stujdy try todetermine the influence of factors influencing consumers' online choices. Thesampling in this research adopts intentional sampling technique, that is, thetechnique of determining samples according to certain standards. Criteria aremales and females aged 19-50 who are college students, students and employeesof Mataram City and have used Gojek or Grab app services. The Datacollection techniques using questionnaires. The data analysis tool used is IBMSPSS Statistics 24. Result show that price, service quality, corporate image,and word of mouth components significantly effects consumers' onlinedecision-making.